PENGARUH STRUKTUR KEPEMILIKAN DAN GENDER DIVERSITY TERHADAP KINERJA KEUANGAN PERUSAHAAN - Septiani, Serli; Puttri, Daniati; Rifa, Dandes (Jurnal Kajian Akuntansi dan Auditing, 2025)
The purpose of this study is to empirically examine the influence of ownership structure and gender diversity on corporate financial performance. The population in this study includes manufacturing companies in the industrial sector listed on the Indonesia Stock Exchange for the years 2018-2022. The sample in this study was determined using purposive sampling techniques, resulting in 135 observations from 27 companies that met the sample criteria. The type of data used in this study is secondary data obtained from annual reports sourced from the official website of the Indonesia Stock Exchange and the official websites of the companies. Hypothesis testing was conducted using multiple linear regression analysis. The results show that female members of the Board of Commissioners have a significant positive effect on corporate financial performance, while managerial ownership, institutional ownership, and female members of the Board of Directors do not affect corporate financial performance.